Piloting a New Model for Treating Music Performance Anxiety: Training a Singing Teacher to Use Acceptance and Commitment Coaching With a Student - Shaw, Teresa A.; Juncos, David G.; Winter, Debbie (Frontiers in Psychology, 2020)
Thus far, treatments for music performance anxiety (MPA) have focused primarily on interventions administered by psychologists and mental health clinicians with training and education in psychotherapy.  While these interventions are promising or even efficacious, many musicians prefer not to work with a psychotherapist due to stigma and lack of time/access. Student musicians are particularly vulnerable to developing MPA, and while they may prefer consulting with their teachers about MPA over psychotherapists, many teachers feel unqualified to help. Here, we investigated an alternative intervention model, in which a clinical psychologist with MPA expertise trained a singing teacher with no training or education in psychotherapy to use an evidence-based coaching model, Acceptance and Commitment Coaching (ACC), with a student vocalist with problematic MPA, in a single-subject design format. ACC is a version of Acceptance and Commitment Therapy (ACT) that has been used under various names with non-clinical populations to help enhance psychological flexibility, e.g., with athletes, at the workplace, with undergraduates, and others. The teacher received approximately seven hours of ACC training via Skype. In turn, she provided six one-hour ACC sessions to a university student vocalist. Materials for the training and coaching sessions were taken from an ACC book and an ACT-based self-help book for musicians, and the teacher also adhered to a GROW model of coaching. The student made clinically significant improvements in two ACT-based processes believed to correlate with improved psychological flexibility in previous ACT for MPA psychotherapy research, i.e., acceptance of MPA-related discomfort and defusion from MPA-related thoughts.  The student also reported a significant shift had occurred in his thinking: he became more willing to have his MPA, and so he volunteered to sing in classes early in the upcoming semester, and he auditioned for & won a lead role in a musical, both of which he previously avoided doing.  ACC appears to be a promising MPA intervention that can be administered by a music teacher without training or education in psychotherapy, and it may help schools who do not employ psychologists and are therefore unable to follow best practice guidelines for treating MPA.